Health professionals and students encounter multi-level barriers to implementing high-value osteoarthritis care: a multi-national study - Briggs, Andrew; Houlding, E.; Hinman, R.S.; Desmond, L.A.; Bennell, K.L.; Darlow, B.; Pizzari, T.; Leech, M.; MacKay, C.; Larmer, P.J.; Bendrups, A.; Greig, A.M.; et al. (ELSEVIER SCI LTD, 2019)
Objective: Consistent evidence-practice gaps in osteoarthritis (OA) care are observed in primary care settings globally. Building workforce capacity to deliver high-value care requires a contemporary understanding of barriers to care delivery. We aimed to explore barriers to OA care delivery among clinicians and students. Design: A cross-sectional, multinational study sampling clinicians (physiotherapists, primary care nurses, general practitioners (GPs), GP registrars; total possible denominator: n = 119,735) and final-year physiotherapy and medical students (denominator: n = 2,215) across Australia, New Zealand and Canada. Respondents answered a survey, aligned to contemporary implementation science domains, which measured barriers to OA care using categorical and free-text responses. Results: 1886 clinicians and 1611 students responded. Items within the domains ‘health system’ and ‘patient-related factors’ represented the most applicable barriers experienced by clinicians (25–42% and 20–36%, respectively), whereas for students, ‘knowledge and skills’ and ‘patient-related factors’ (16–24% and 19–28%, respectively) were the most applicable domains. Meta-synthesis of qualitative data highlighted skills gaps in specific components of OA care (tailoring exercise, nutritional/overweight management and supporting positive behaviour change); assessment, measurement and monitoring; tailoring care; managing case complexity; and translating knowledge to practice (especially among students). Other barriers included general infrastructure limitations (particularly related to community facilities); patient-related factors (e.g., beliefs and compliance); workforce-related factors such as inconsistent care and a general knowledge gap in high-value care; and system and service-level factors relating to financing and time pressures, respectively. Conclusions: Clinicians and students encounter barriers to delivery of high-value OA care in clinical practice/training (micro-level); within service environments (meso-level); and within the health system (macro-level).